Pengaruh Persepsi Kemudahan Penggunaan Fasilitas Uang Elektronik Terhadap Keputusan Menggunakan Untuk Belanja Mahasiswa Fakultas Ekonomi Universitas Negeri Padang di Masa Pandemi Covid – 19 - Rezky Putri Yunusi; Friyatmi Friyatmi (Jurnal Ecogen, 2022)
This study aimed to determine whether there is an effect of perceived ease of use of electronic money facilities on the decision to use for shopping by students of the Faculty of Economics, Padang State University. This is descriptive associative research. The population were students of the Faculty of Economics, Padang State University and 97 students were selected. The sampling technique was purposive sampling. The data used are primary and secondary data. Data were collected using questionnaire. It was analyzed using, simple regression. The results of this study indicate that the perceived ease of use of electronic money has a significant positive effect on the decision to use it for shopping. The effect of perceived ease of use on the decision to use electronic money for shopping has a contribution of 61%.Keywords : perceived ease of use, decision to use